2013
DOI: 10.1111/jeu.12058
|View full text |Cite
|
Sign up to set email alerts
|

A New Heterotrophic Dinoflagellate from the North‐eastern Pacific, Protoperidinium fukuyoi: Cyst–Theca Relationship, Phylogeny, Distribution and Ecology

Abstract: The cyst-theca relationship of Protoperidinium fukuyoi n. sp. (Dinoflagellata, Protoperidiniaceae) is established by incubating resting cysts from estuarine sediments off southern Vancouver Island, British Columbia, Canada, and San Pedro Harbor, California, USA. The cysts have a brown-coloured wall, and are characterized by a saphopylic archeopyle comprising three apical plates, the apical pore plate and canal plate; and acuminate processes typically arranged in linear clusters. We elucidate the phylogenetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 52 publications
5
32
0
Order By: Relevance
“…S1). Molecular phylogenies suggested that most of these sections were monophyletic and were nested within the Protoperidinium sensu stricto clade (Mertens et al 2013). There were only two exceptions: the section Conica was polyphyletic and positioned within the Protoperidinium clade (Yamaguchi et al 2006), and the section Oceanica was monophyletic but positioned outside of the Protoperidinium sensu stricto clade (Sarai et al 2013).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…S1). Molecular phylogenies suggested that most of these sections were monophyletic and were nested within the Protoperidinium sensu stricto clade (Mertens et al 2013). There were only two exceptions: the section Conica was polyphyletic and positioned within the Protoperidinium clade (Yamaguchi et al 2006), and the section Oceanica was monophyletic but positioned outside of the Protoperidinium sensu stricto clade (Sarai et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Protoperidinium and Archaeperidinium with a transitional plate generally have a saphopylic or theropylic 2a archeopyles, respectively (Harland 1982;Ribeiro et al 2010;Mertens et al 2012); whereas, those Protoperidinium species without a transitional plate have a compound archeopyle involving 2 0 -4 0 (Lewis & Dodge 1987;Kawami & Matsuoka 2009;Kawami et al 2009;Mertens et al 2013;Liu et al 2014). Cyst morphology can be diverse and is used to classify cysts within various cyst genera, e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, higher fluxes of cysts of P. fukuyoi were also recorded in the Santa Barbara Basin under similar circumstances, when a short, secondary upwelling pulse interrupted relaxed upwelling conditions (Bringué et al, 2013). Other sediment trap records of P. fukuyoi cyst production from the Strait of Georgia and Saanich Inlet (Price and Pospelova, 2011) in the productive waters of coastal southwestern Canada also indicate higher fluxes during the warmest months of the year (Mertens et al, 2013). 25…”
Section: Interactions Between Dinoflagellates and Other Major Planktomentioning
confidence: 83%
“…The dinoflagellate cyst nomenclature follows the paleontological taxonomy system provided in Lentin and Williams (1993) (recently updated in Williams et al, 2017) and conforms to taxonomic descriptions provided by Margalef (1961), Wall and 15 Dale (1966, 1968, 1969, Reid (1977), Matsuoka et al (1990, 2006), Zonneveld (1997, Ellegaard and Moestrup (1999), Head (1996Head ( , 2002, Rochon et al (1999), Zonneveld and Jurkschat (1999), Verleye et al (2011), Mertens et al (2013) and Liu et al (2015), with most cyst description summaries and corresponding motile dinoflagellate names provided in Zonneveld and Pospelova (2015).…”
Section: Dinoflagellate Cyst Nomenclaturementioning
confidence: 99%
“…) and Barrow Strait, Nunavik, Canada (Mertens et al. ). The ITS rDNA was identical for specimens of I. minutum subsp.…”
Section: Resultsmentioning
confidence: 99%